2020
DOI: 10.1007/s11420-020-09805-0
|View full text |Cite
|
Sign up to set email alerts
|

The Utilization of Regional Anesthesia among Pediatric Patients: A Retrospective Study

Abstract: Background The use of regional anesthesia (RA) in pediatric patients remains understudied, although evidence suggests benefits over general anesthesia. Questions/Purposes We sought to identify factors associated with RA use in patients under the age of 21 years undergoing ambulatory orthopedic surgery. Methods Patients under the age of 21 who underwent anterior cruciate ligament (ACL) repair or reconstruction, knee arthroscopy (KA), or shoulder arthroscopy (SA) were identified from the NY Statewide Plannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…These have been well described in the management of ACL injuries and fractures. 24 25 26 27 28 Cultural differences in seeking care and trust in the medical establishment, which have already been shown to vary between racial groups based on historic and present experiences, 29 30 31 32 33 34 may also have factored into families' decisions to seek care for less severe sports injuries during the pandemic. Given these known disparities regarding both the COVID-19 and pediatric orthopaedic care, it is possible that similar issues played a role in the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…These have been well described in the management of ACL injuries and fractures. 24 25 26 27 28 Cultural differences in seeking care and trust in the medical establishment, which have already been shown to vary between racial groups based on historic and present experiences, 29 30 31 32 33 34 may also have factored into families' decisions to seek care for less severe sports injuries during the pandemic. Given these known disparities regarding both the COVID-19 and pediatric orthopaedic care, it is possible that similar issues played a role in the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…22 However, some studies have found racial disparities in the utilization of regional anesthesia. 23,24 In a study of 1,062,152 hip and knee arthroplasty procedures, there was a significant difference between patients of color versus White patients in the utilization of regional anesthesia. 24 Patients with Medicaid or without insurance were also less likely to receive a block.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of regional anesthesia in perioperative pain control regimens has been shown to be superior to opioid or non-opioid analgesic modalities alone ( 4 6 ). However, some studies have shown ethnic-based disparities in the use of regional anesthesia ( 1 , 7 – 11 ). For example, in a retrospective study of 639 patients in an enhanced recovery program, the use of epidural anesthesia or transversus abdominis plane (TAP) blocks was 13% lower in non-White patients than in White patients ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…A similar observation was made in 81, 345 patients who had undergone mastectomy, where compared to White patients, the odds of receipt of regional anesthesia was up to 21% lower in non-White patients ( 9 ). Potential reasons for these disparities have included implicit bias ( 1 , 8 , 11 ), language barriers ( 10 , 11 ), and cultural preferences ( 11 ).…”
Section: Introductionmentioning
confidence: 99%